FORMULATION AND TEST OF ANTIBACTERIAL Staphylococcus aureus PAPERSOAP SOURSOP’S LEAVES EXTRACT (Annona muricata L.) WITH VARIATIONS OF GLYCERIN AS PLASTICIZER - Vivin Nopiyanti; Din Samsudin; Anita Nilawati (Jurnal Farmasi (Journal of Pharmacy), 2022)
Papersoap is a thin printed solid soap product as a unique innovation because it resembles paper. Soursop leaves contain flavonoid compounds, tannins, alkaloids and saponins that are useful as antibacterial. preparations papersoap with soursop leaf extract require glycerin as a plasticizer is believed to produce good physicochemical properties. This study aims to determine the physical quality of papersoap from the effect of soursop leaf extract and variations of glycerin and to test the antibacterial activity of the Papersoap against Staphylococcus aureus ATCC 25923.Soursop leaf extract was obtained by maceration method with 96% ethanol as solvent. The concentration of soursop leaf extract 5% was formulated into papersoap with three variations of glycerin formula, namely 10%, 15%, and 20%.preparation papersoap includes organoleptic, pH, homogeneity, foam stability, water content, and free alkali tests which have passed the curing for two weeks as the preparation evaluation stage. Antibacterial activity test against Staphylococcus aureus ATCC 25923 using well diffusion method. The data obtained were processed using Shapiro-wilk, one way ANOVA/Kruskal.The results showed that the formula of the papersoap preparation of soursop leaf ethanol extract (Annona muricata L.) with glycerin variations can provide differences in the physical quality of papersoap preparations and have an inhibitory diameter against Staphylococcus aureus bacteria ATCC 25923 successively 25.26; 24,67; 23.47 mm